SIFAT KIMIA, FUNGSIONAL DAN REOLOGI PATI AREN FOSFAT PADA KOMBINASI KONSENTRASI PATI AREN DAN WAKTU REAKSI YANG BERBEDA - Abdul Rahim; Gatot Siswo Hutomo; Syahraeni Kadir; Nur Alam; Abd Hamid; Jusman Jusman (Jurnal Pengolahan Pangan, 2018)
The objectives of the study were to obtained the optimal combination of starch concentration and reaction time in the synthesis of phosphorylated arenga starches. Synthesis of phosphorylated arenga starches using sodium tripolyphosphate reagents and arenga starch 20 and 30% (b/v) with variations of time reaction 30 and 45 min. Chemical, functional and rheological characteristics of phosphorylated arenga starcheswere investigated i.e. percent phosphate and degree of substitution (DS), binding of phosphate groups using FourierTransform Infrared (FTIR), water and oil holding capacity (WHC, OHC), swelling power and solubility and emulsion separation volume. The results showed a combination of 30% arenga straches with a reaction time 45 min were optimal combination that to produced phosphorylated arenga starches with the highest of phosphate content (2.710%) and DS 0.147. The FTIR spectra of phosphorylated arenga starches have been a change in vibration of OH groups that replace the reaction of phosphate groups with OH in starch molecules. WHC and swelling power increased, but solubility phosphorylated arenga starches decreased with the in increasing combination of arenga starch concentration and reaction time. The emulsion separation volume the most stable at the combination of highest arenga starch concentration and the long reaction time. Phosphorylated arenga starches which produced were used as emulsifiers for food aplication